Examining the Complications of Global Energy Governance - SOVACOOL, Benjamin K. (Institutional Knowledge at Singapore Management University, 2012)
This article systematically examines fundamental obstacles to effective and efficient global energy governance. The first part of the article defines and conceptualises governance, global governance and global energy governance. It also explores the existing global energy governance architecture, depicting six types of global energy governor – intergovernmental organisations, summit processes, international non-governmental organisations, multilateral financial institutions, regional organisations that involve two or more countries as members and hybrid entities – and a sample of 42 such institutions and organisations currently operating around the world. The second part of the article corrects some emerging misconceptions about global energy governance: that effective forms of governance are likely to occur because they have net benefits; that Western forms of energy governance can be transplanted to the rest of the world; and that regional energy governance is in some ways preferable to global energy governance. The article concludes that more nuanced and careful assessment will be needed, and misconceptions abandoned, if we are truly to respond to the governance issues induced by deteriorating energy security and growing emissions of greenhouse gases.